"تأثير إدارة المخاطر المالية على استدامة صناديق الضمان الاجتماعي" (Comprehensive Journal of Science, 2026)
This study aimed to identify the impact of financial risk management on the financial sustainability of social security funds by determining the types of risks they face, evaluating the level of application of risk management methods, analyzing the effectiveness of adopted policies, and measuring their reflection on financial sustainability, ultimately leading to recommendations to enhance the efficiency of risk management. The study population consisted of employees at the Social Security Fund in Al-Bayda, and the sample included all employees across different departments, with 52 valid questionnaires available for analysis. The study relied on questionnaires as a tool for data collection, and the data were analyzed using descriptive and inferential statistical methods through the SPSS program. The results showed a high level of awareness of the importance of financial risk management and its role in supporting sustainability, while indicating financial and organizational challenges, most notably the electronic deficit, and some weakness in technical capacities. In addition, there was an acceptable level of policy implementation and evaluation procedures, alongside a need for further institutional development. The study recommended strengthening financial risk management strategies, diversifying investments, developing human competencies, and improving governance and financial oversight in a way that supports the long-term financial sustainability of social security funds.